Life quality and rehabilitation after a road traffic crash: A literature review. (July 2016) - Üzümcüoğlu, Yeşim; Özkan, Türker; Lajunen, Timo; Morandi, Anna; Orsi, Chiara; Papadakaki, Maria; Chliaoutakis, Johannes
Highlights: Literature review includes 114 publications focusing on post-Road Traffic Crashes. TBIs, spinal cord injuries, and orthopedic injuries are mostly frequent after RTIs. Impact of the event plays an important role in PTSD. However, the IES should be upgraded. Different groups may have different antecedents and rehabilitation program after a RTC. Informal support systems in post-traumatic care have mostly been ignored in literature. Abstract: Road traffic injuries continue to pose a worldwide threat to health and well-being of people. In European Union, for example, each year more than 25, 000 people are killed and 1.4 million people are injured or disabled in road traffic crashes (RTCs). Additionally, families of RTC victims and their lives are affected emotionally, socially, psychologically, and economically. It should be noted that as in the beginning of 1990s, however, the majority of available literature is focused on the pre-RTC factors (e.g., prevention) rather than the post-RTCs (e.g., the rehabilitation of severely injured) period. As a result, disproportionally greater weight is attached on the pre-RTCs internationally whereas little is known about the psycho-social and economic burden of the post-RTCs period. In this paper, a literature review including the years 1990–2013 was conducted on the publications about post-RTCs period to investigate the possible problems that prevents studying the life quality and rehabilitation after RTCs. Trauma, traffic, injury, rehabilitation, and satisfaction (related to the services and process) were used as keywords and Scopus database (www.scopus.com ) was used for searching. In the first step, 443 publications were obtained. Among 443 publications, 75 publications were recorded as relevant. In addition, three publications were suggested by co-authors and 37 publications were obtained by a book source suggested by the reviewer. A total number of 114 publications are presented and evaluated under different components or "stages" of the post-RTCs' period related to rehabilitation as (a) service utilization indicators (e.g., length of care) and service satisfaction indicators (e.g. satisfaction from services), (b) morbidity indicators (e.g., injury patterns), (c) quality of life indicators (e.g., physical and psychological well-being indicators), (d) social network indicators (e.g., type and frequency of informal care provided by family members), and (e) cost indicators (e.g., overall expenditure). The overall evaluation of the publications in literature, possible implications, suggestions, and future directions were discussed.